KOMPOSISI KIMIA, SIFAT FISIK DAN SIFAT SENSORIS SOSIS DAGING AYAM PETELUR AFKIR DENGAN PENAMBAHAN KARAGINAN - , TIA YUSDANIA WARDANI, Ir. Jamhari, M.Agr.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this study was to investigate the effect of carrageenan (seaweed powder) at different levels on the chemical composition, physical properties and sensory properties of spent hen sausage. The materials used in the study were spent hen meat, tapioca starch, carrageenan, skim milk, ice cubes, and spices. Research treatment was addition of carrageenan on the sausage formula at levels of 0.0, 1.5, 2.0, 2.5, and 3.0%. Replication of each treatment was six times. The observed variables were the chemical composition, physical properties and sensory properties. Data of chemical composition and physical properties were analyzed by analysis of variance one way classification, continued by Duncan's New Multiple Range Test. Data of sensory properties were analyzed by non-parametric statistical analysis with Hedonic Kruskal Wallis test. The results showed that the addition of carrageenan up to level 3.0% significantly affected (P<0,05) decreased tenderness but not pH value of spent hen sausage. Furthermore the addition of carrageenan on the sausage formula also have no effect significant on the chemical composition (moisture and protein content), as well as sensory properties (colour, texture, flavour, smell, and acceptability) of spent hen sausage.